Diastereoselective Cyclobutenol Synthesis: A Heterogeneous Palladium‐Catalyzed Oxidative Carbocyclization‐Borylation of Enallenols. Issue 1 (5th November 2018) - Li, Man‐Bo; Posevins, Daniels; Gustafson, Karl P. J.; Tai, Cheuk‐Wai; Shchukarev, Andrey; Qiu, Youai; Bäckvall, Jan‐E.
Abstract: A highly selective and efficient oxidative carbocyclization/borylation of enallenols catalyzed by palladium immobilized on amino‐functionalized siliceous mesocellular foam (Pd‐AmP‐MCF) was developed for diastereoselective cyclobutenol synthesis. The heterogeneous palladium catalyst can be recovered and recycled without any observed loss of activity or selectivity. The high diastereoselectivity of the reaction is proposed to originate from a directing effect of the enallenol hydroxyl group. Optically pure cyclobutenol synthesis was achieved by the heterogeneous strategy by using chiral enallenol obtained from kinetic resolution. Abstract : Heterogeneous catalysis : An oxidative carbocyclization‐borylation of enallenols catalyzed by recoverable and recyclable heterogeneous Pd‐AmP‐MCF catalyst was developed for the synthesis of cyclobutenols with high diastereoselectivity (see scheme).